Juvenile Dysplasia Epiphysealis Hemimelica with Multiple Ankle Free Body - Shinsuke Sato; Song Ho Chang; Taro Kasai; Yuji Maenohara; Sho Yamazawa; Sakae Tanaka; Takumi Matsumoto (Case Reports in Orthopedics)
Dysplasia epiphysealis hemimelica (DEH), also known as Trevor’s disease, is a rare overgrowth of cartilage that commonly arises in the epiphyseal bone of children. We report a rare case of DEH originating from a talus accompanied by multiple intra-articular free bodies in a 7-year-old patient with ankle instability. After the primary surgery for free body removal and microfracture technique for the cartilage defects in the ankle joint, the free body recurred. Secondary surgery of arthroscopic free body removal with lateral ankle ligament repair succeeded in treating the patient, without further recurrence of the free body.